(3cTa CSQGQ GdJhQGI hJYQjHgGs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf hYdjg CJhcd GNQGL eYGfi GdcJGH GdebOS ef cJH GdfHhI GdeSei GdJhQGI ai GddZI GdbOjeI s
(3BNQgG (B:s
(3hSGFQ GdeNGha GdYXjeI GdJi UfYgG ehSi Ydjg GdSdGe HMaQ JLejY GdESQGA hGdSdGe Ke TQM GdJhQGI GdYde hfGXQ gPG GdcJGH HbhI s
(3GdfSNI HgG MhGTs
(3cJH ai CNQgG (B"(3Je TQM GdJhQGI eY Cfg JQLeI GdJhQGIs
(3fSNI ecQQI Yf (B37 (3cJH SeGhjI (B"(3cTa CSQGQ GdJhQGI(B"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcJH GdSeGhjIs